2018
DOI: 10.1016/j.neo.2018.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genomic Alteration in Primary Central Nervous System Lymphoma and the Expression of Some Related Genes

Abstract: Primary central nervous system lymphoma (PCNSL) is a rare and special type of non-Hodgkin lymphoma. The treatment of PCNSL is comprehensive, combining surgery, radiotherapy, and chemotherapy. However, the outcome is poor because of its high invasiveness and rate of recurrence. We analyzed 22 cases of PCNSL using next-generation sequencing (NGS) to detect 64 candidate genes. We used immunohistochemical methods to analyze gene expression in 57 PCNSL samples. NGS showed that recurrent mutations in KMT2D and CD79B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 78 publications
(85 reference statements)
4
41
1
Order By: Relevance
“…1,79 Isolated MYC, BCL2 or BCL6 rearrangements are uncommon, but have been reported at low frequency. 80 Zhou et al 81 meticulously categorised mutations encountered in DLBCL-CNS into eight cellular pathways. NF-kB, B-cell receptor signalling, epigenetic modulation and apoptosis regulation are involved.…”
Section: Immunophenotypementioning
confidence: 99%
See 1 more Smart Citation
“…1,79 Isolated MYC, BCL2 or BCL6 rearrangements are uncommon, but have been reported at low frequency. 80 Zhou et al 81 meticulously categorised mutations encountered in DLBCL-CNS into eight cellular pathways. NF-kB, B-cell receptor signalling, epigenetic modulation and apoptosis regulation are involved.…”
Section: Immunophenotypementioning
confidence: 99%
“…NF-kB, B-cell receptor signalling, epigenetic modulation and apoptosis regulation are involved. 78,81 PIM1, MYD88, CD79B, and CDKN2A are among the most common genes mutated, some of which can be attributed to somatic hypermutation. 82 TP53 mutations have been identified in 27-37% of cases.…”
Section: Immunophenotypementioning
confidence: 99%
“…The results suggest that PIM1 is mainly expressed in the nucleus, while MYD88 staining is largely cytoplasmic, with almost no nuclear staining. Compared with the control group, the positive expression rates of PIM1 and MYD88 were higher in PCNSL, and their expression levels were positively correlated (r = 0.581, P = 2.0 × 10 -6 ) [19].…”
Section: Survival Analysis Based On Expression Of High-frequency Genesmentioning
confidence: 80%
“…NF-κB signaling was also found hyper-activated in immune-rich PCNSL. Previous studies have shown that MYD88 gene mutations are highly prevalent and support lymphoma growth through NF-κB signaling in PCNSL [10][11][12][13]. It would hence be reasonable to co-assess the genomic and immune phenotypic statuses of PCNSL to propose combined ibrutinib/ICI therapies to immune rich/MYD88-mutated PCNSL patients (ongoing trial NCT03770416).…”
Section: Discussionmentioning
confidence: 99%
“…Significant efforts have been devoted to the identification of common genetic alterations and activating oncogenic signaling in PCNSL [7][8][9][10][11][12][13][14]. These alterations mainly involve Nuclear factor-kappa B (NF-κB), B cell receptor (BCR), Toll-like receptors (TLR), Mitogen-activated protein kinase (MAPK) signaling, the DNA damage response, apoptosis, and cell cycle control.…”
Section: Introductionmentioning
confidence: 99%